Structure identification of potential compound as selective renal anticancer isolated from Nerium indicum Mill. Leaves - Mae S.H. Wahyuningsih; Sofia Mubarika; Mark T. Hamann; Ibnu G. Gandjar; Subagus Wahyuono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Oleandrin is one of cardenolida compound isolated from an active fraction of Nerium indicum Mill leaves. (fam. Apocynaceae), which have cytotoxic effect on several human cancer cells, and also to normal cells in vitro. Another compound which was potential as renal anticancer has also been isolated from N. indicum. However, its chemical structure has not been discovered. The aim of this study was to identify the potential compound as selective to renal cancer present in the leaves of N. indicum.The potential compound was isolated from the active fraction using Preparative TLC and structure elucidation was done by using spectroscopic methods (UV, IR, MS and NMR).Base on this spectra and by comparison with oleandrin data, it was indicated that the potential compound as Renal anticancer was as 16,17-dehydrodeacetyl-5a-oleandrin.Key word: N.indicum, oleandrin, cytotoxic, renal anticancer, spectroscopic